Omega 3 Fatty Acid and Skin Diseases - Sawada, Yu; Saito-Sasaki, Natsuko; Nakamura, Motonobu (Frontiers in Immunology, 2021)
Humans are exposed to various external environmental factors. Food intake is one of the most influential factors impacting daily lifestyle. Among nutrients obtained from foods, omega-3 polyunsaturated fatty acids (PUFAs) have various beneficial effects on inflammatory diseases. Furthermore, omega-3 PUFA metabolites, including resolvins, are known to demonstrate strong anti-inflammatory effects during allergic and inflammatory diseases; however, little is known regarding the actual impact of these metabolites on skin diseases. In this review, we focused on metabolites that have strong anti-inflammatory actions in various inflammatory diseases, as well as those that present antitumor actions in malignancies, in addition to the actual effect of omega-3 PUFA metabolites on various cells.